Should carbohydrate concentration of a sport drink be less than 8% during exercise in the heat - Millard-Stafford, M. L.; Sparling, P. B.; Rosskopf, L. B.; Snow, T. K. (International Journal of Sport Nutrition and Exercise Metabolism, 2005)
Our purpose was to determine if sports drinks with 6 and 8% CHO differentially affect physiological responses or run performance in the heat. Ten men ran 32 km while ingesting: placebo (P), 6% carbohydrate-electrolyte (CE6), and 8% carbohydrate-electrolyte (CE8). At 15 km, a 250 mL drink labeled with deuterium oxide (D2O) was ingested. Blood glucose and respiratory exchange ratio were significantly higher (P < 0.05) for CE6 and CE8 compared to P. Rectal temperature (T(re)) at 32 km was higher for CE8 (40.1 +/- 0.2 degrees C) compared to P (39.5 +/- 0.2 degrees C) but similar to CE6 (39.8 +/- 0.2 degrees C). D2O accumulation was not different among drink trials. Run performance was 8% faster for CE8 (1062 +/- 31 s) compared to P (1154 +/- 56 s) and similar to CE6 (1078 +/- 33 s). Confirming the ACSM Position Stand, 8% CE are acceptable during exercise in the heat and attenuate the decline in performance.